ANALYSIS OF COLLECTION MANAGEMENT IN THE SPECIAL LIBRARY OF THE BENGKULU REGIONAL OFFICE OF THE MINISTRY OF LAW AND HUMAN RIGHTS - Guna, Chandra Hari; Purwaka, Purwaka; Valentino, Rahmat Alifin (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2025)
This study aims to analyze collection management at the Special Library of the Bengkulu Regional Office of the Ministry of Law and Human Rights and identify obstacles faced in the management process. The focus of the study includes aspects of planning, policy, collection relevance, accessibility, and collection maintenance. The research method used is a qualitative descriptive method with data collection techniques through observation, interviews, and documentation. Research informants in this study include the head of the sub-division that oversees the library, library managers, and users. The theory used as a basis is the Collection Life Cycle Theory which explains the life cycle of library collections from selection, acquisition, organization, use, to maintenance and weeding of collections. The results of the study indicate that the collection management system in this library still faces various obstacles, such as the classification and cataloging process is not yet optimal, there is no periodic evaluation of the collection, and limited experts in the library field. In addition, collection accessibility is still limited because there is no adequate digital search system. In terms of maintenance, the library has not implemented an effective collection weeding system, so that many old collections are still stored on shelves that have not been updated according to the needs of users. Based on these findings, this study recommends improving the quality of collection management through the recruitment of library experts, the development of digital systems to improve the accessibility of collections, and the preparation of more systematic written policies regarding collection management. Periodic evaluation of the collection also needs to be carried out to ensure that the collection remains relevant to the needs of users. With these improvements, it is hoped that the Special Library of the Bengkulu Regional Office of the Ministry of Law and Human Rights can provide more effective and efficient services in supporting the legal information needs of employees and the general public.